2007
DOI: 10.1002/bmc.945
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the development of derivatization reagents having a benzofurazan structure

Abstract: Chemical derivatization is often used to enhance the detectability of the target compounds and to improve the separation efficiency in high-performance liquid chromatography (HPLC). In this review, we describe the recent progress in the development of derivatization reagents having a benzofurazan structure, namely, the fluorogenic reagents, water-soluble reagents, reagents for the analysis of peptides and proteins, and reagents for mass spectrometric detection. The application of these reagents to bio-samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 84 publications
1
21
0
Order By: Relevance
“…To date, several reports have described that the benzofurazan moiety mentioned above is useful not only for fluorescence, but also for MS detection 19,20. Therefore, here, we changed the detection system from a fluorescence to MS system, using a JMS-T100 LP AccuTOF LC-Plus equipped with an ESI source (JEOL Co. Ltd., Tokyo, Japan), as an alternative detection method.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several reports have described that the benzofurazan moiety mentioned above is useful not only for fluorescence, but also for MS detection 19,20. Therefore, here, we changed the detection system from a fluorescence to MS system, using a JMS-T100 LP AccuTOF LC-Plus equipped with an ESI source (JEOL Co. Ltd., Tokyo, Japan), as an alternative detection method.…”
Section: Resultsmentioning
confidence: 99%
“…To the EditorSome recent articles published in the literature provide a great impetus for the continued outside-the-box thinking in the development and applicability of novel reagents for HPLC-and LC/MS-related applications (Santa et al, , 2008aSeiwert and Karst, 2007;Al-Dirbashi et al, 2007;Honda et al, 2007;Timperio et al, 2007;Hammad et al, 2007;Farid et al, 2007;Gao et al, 2005;Halket et al, 2005;Johnson, 2005;Higashi and Shimada, 2004).…”
Section: New Thinking In the Development Of Novel Derivatization Reagmentioning
confidence: 99%
“…As eloquently captured by a recent work on benzofuran based derivatization reagents, Santa et al (2008a) have enumerated several different options for bioanalytical specialists to exploit, including LC/MS/MS options via ESI. The detailed requirements for LC/ESI-MS/MS derivatization reagents to be excellent have been summarized (Santa et al, , 2008a.…”
Section: New Thinking In the Development Of Novel Derivatization Reagmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the relationship between the chemical structure and fragment patterns of benzofurazan compounds and found that benzofurazan compounds having an (N,N-dimethylamino)ethylaminosulfonyl group [-SO 2 NHCH 2 CH 2 N(CH 3 ) 2 ] and an amino group were easily cleaved by CID and generated a single and intense production at m/z 151 in MS/MS (Santa et al, 2007b;2008a). Based on these observations, we have synthesized benzofurazan derivatization reagents suitable for LC/ESI-MS/MS, i.e.…”
Section: Introductionmentioning
confidence: 99%